Maternal executive functioning is associated with infant sustained attention, but not executive functioning, in a sex-specific manner - Karonen Anniina; Kataja Eeva-Leena; Bridgett David J.; Paunio Tiina; Kantojärvi Katri; Korja Riikka; Karlsson Hasse; Karlsson Linnea; Nolvi Saara (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Parental executive functioning (EF) is considered one key contributing source, via direct and indirect routes, of inter-individual variation in offspring EF. The current study investigated the unexplored associations between maternal EF and infant EF as well as its precursor, sustained attention. Ninety-seven mother-infant-dyads from the FinnBrain Birth Cohort Study participated. Maternal EF was assessed using selected measures from the Cogstate test battery. At 8 months, infants completed Lab-TAB Blocks and modified A-not-B tasks. A modest but robust link between maternal EF and infant attention was revealed in girls. There was no association between mother and infant EF in either sex at 8 months. Notable directions for future research, and potential underlying mechanisms of sex differences are discussed.